Electricity generation and multi-purpose applications from biogas and biomethane - Kabeyi, Moses Jeremiah Barasa; Akpan, Joseph; Olanrewaju, Oludolapo Akanni (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Biogas produced from biomass is a renewable energy resource with high value potential to support sustainable development. This study presents abridged advances and pathways from biogas and biomethane to electricity with opportunities and challenges in generation, conversion, and storage needed for use in many areas like transportation, power generation and storage, building, and industrial heat production sectors. A high knock resistance, making it suitable for use in thermal systems with high compression rate, characterizes biogas combustion. Various prime movers using biogas as fuel can be used for electricity generation, including direct conversion through fuel cells, which is a significant pathway to sustainable energy storage. Biogas to electricity conversion by a generator set is much more practical today. Turbines, micro turbines, Stirling engines, diesel engines, and petrol engines are only some of the viable possibilities for converting biogas to electricity. Biomethane can be used as a substitute for natural gas in all its applications with little or no modifications to the fuel infrastructure. Finally, this study discusses biogas and biomethane’s limits and contribution to the Sustainable Development Goals 2, 6, 7, 8, 9, 11, 13, 14, and 17.